The Influence Of Income Level, Education, And Public Perception On Interest In Cash Waqf - Nabila, Nisa; Nirlina, Eka; Umuri, Khairil (Risalah Iqtishadiyah, 2024)
This study aims to determine the influence of income, education and perception on interest in cash waqf in Aceh Besar district. The data used were primary data using a questionnaire instrument distributed to 100 community respondents with ID cards in Aceh Besar. The number of variables studied there are 4 variables, namely income level, education and perception as independent variables and variables of interest in cash waqf as dependent variables. The approach used in this study is a quantitative approach. The sampling method used is nonprobability sampling with purposive sampling techniques. Analysis methods used with multiple linear regression analysis. The results showed that income and perception had a positive and significant effect on the interest of the people with cash waqf, while education did not have a positive and significant effect on the interest of people with cash waqf. The findings of this study indicate that to increase public interest in cash waqf, it is necessary to increase understanding of cash waqf through socialization and other activities.